2022
DOI: 10.3892/mmr.2022.12670
|View full text |Cite
|
Sign up to set email alerts
|

The GABAB receptor agonist STX209 reverses the autism‑like behaviour in an animal model of autism induced by prenatal exposure to valproic acid

Abstract: Autism spectrum disorder (ASD) is a lifelong neurodevelopmental condition characterized by impaired social interaction, compromised communication, and restrictive or stereotyped behaviours and interests. Due to the complex pathophysiology of ASD, there are currently no available medical therapies for improving the associated social deficits. Consequently, the present study investigated the effects of STX209, a selective γ-aminobutyric acid type B receptor (GABABR2) agonist, on an environmental rodent model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…Thus, elevated PE in the frontoparietal region may reduce exploratory behavior. In accord with this nding, a valproic acid-induced autistic mouse model with elevated PE in the cortex, hippocampus, thalamus, hypothalamus, cerebellum, and brain stem [29] also spent less time in the central region of the OF [30] as well as reduced exploratory activity [31] compared to control mice.…”
Section: Effects Of Brain Phospholipid Moieties On Locomotor Activity...supporting
confidence: 67%
“…Thus, elevated PE in the frontoparietal region may reduce exploratory behavior. In accord with this nding, a valproic acid-induced autistic mouse model with elevated PE in the cortex, hippocampus, thalamus, hypothalamus, cerebellum, and brain stem [29] also spent less time in the central region of the OF [30] as well as reduced exploratory activity [31] compared to control mice.…”
Section: Effects Of Brain Phospholipid Moieties On Locomotor Activity...supporting
confidence: 67%
“…Table 3 summarizes the findings of each article. 16 Yes Yes Yes NR NR Yes NA NA Yes Yes Yes Yes Yes Yes Canal 2015 17 Yes Yes Yes Yes Yes Yes NA NA Yes Yes Yes Yes Yes Yes Mohammadi 2019 18 Yes Yes Yes Yes Yes Yes NA NA Yes Yes Yes Yes Yes Yes Jiang 2022 19 Yes Yes Yes NR NR Yes NA NA Yes Yes Yes Yes Yes Yes Jiang 2022 20 Yes Yes Yes Yes Yes Yes NA NA Yes Yes Yes Yes Yes Yes Silverman 2015 21 Yes Yes Yes Yes Yes Yes NA NA Yes Yes Yes Yes Yes Yes Venkatachalam 2021 22 Yes Yes Yes NR NR Yes NA NA Yes Yes Yes Yes Yes Yes Yang 2021 23 Yes Yes Yes NR NR Yes NA NA Yes Yes Yes Yes Yes Yes Yang 2021 24 Yes Yes Yes NR NR Yes NA NA Yes Yes Yes Yes Yes Yes Yoshimura 2017 25 Yes Yes Yes Yes Yes Yes NA NA Yes Yes Yes Yes Yes Yes…”
Section: Resultsmentioning
confidence: 99%
“…Muscarinic acetylcholine receptors (mAChRs), coupled to the G protein, have excitatory and inhibitory functions in the central nervous system, being part of postsynaptic excitation and pre and postsynaptic inhibition, even possessing mechanisms of self-inhibition 78 . There is evidence that these receptors can also modulate dopaminergic activity in some brain areas, such as the dorsal striatum, which has been associated with the development of stereotypes 19,79 . O Oxytremonine (mAChR agonist) causes decreased selfgrooming behavior in BTBR mice 80 .…”
Section: Acetylcholinementioning
confidence: 99%
See 1 more Smart Citation
“…This imbalance was proved by genetic analysis of the expression of the functional genes responsible for the inhibitory function and post-mortem and animal studies that demonstrated the reduction of the inhibitory neurons[ 33 ]. Treating this imbalance using medications that boost GABAergic signaling, such as certain antiepileptics, benzodiazepines, and GABAB receptor agonist STX209, has been proven effective in treating some autism symptoms, with variable degrees of success[ 34 ].…”
Section: Discussionmentioning
confidence: 99%